Perceptions and attitudes of residents toward small-scale longline tuna fishing in the Galapagos Marine Reserve: conservation and management implications - Castrejón, Mauricio; Defeo, Omar (Frontiers in Marine Science, 2023)
Longlining represents a cost-effective fishing modality for catching tuna, but its use is contentious due to the unintended catch of endangered, threatened, and protected (ETP) species. In 2000, longlining was banned in the Galapagos Marine Reserve, Ecuador. Since then, local small-scale fishers have contested this decision. In contrast, longlining ban supporters argue that this regulation is fundamental for conserving ETP species, despite scientific and anecdotal evidence indicating that its effective implementation is unfeasible. We conducted an online survey to investigate Galapagos residents’ perceptions concerning longlining, its ecological impact, and diverse potential management strategies. Our findings revealed misconceptions about longline fishing, which highlight the need for improved public awareness and education regarding longline fishing practices, their impact on ETP species, and possible solutions to this complex social-ecological problem. Our study also highlights Galapagos residents’ openness to find a solution that addresses both fishers’ livelihoods and the conservation of ETP species. Galapagos residents are receptive to implementing evidence-based solutions, including testing new bycatch mitigation methods and more selective fishing gears, enhancing monitoring and enforcement, and creating market-based incentives that encourage progressive and adaptive improvements in fishing practices. To solve the Galapagos longline controversy, we recommend a holistic, adaptive, and evidence-based approach that encourages stakeholders to engage in open dialogue, fosters cross-sector collaboration, and promotes research, communication, and educational initiatives. By raising awareness through comprehensive, rigorous, and unbiased scientific information, this ecosystem-based management approach aims to ensure the sustainable development of the small-scale tuna fishery, while conserving the Galapagos’ invaluable and unique marine biodiversity.